2021
DOI: 10.1038/s41598-021-93829-x
|View full text |Cite
|
Sign up to set email alerts
|

Lethal coalitionary attacks of chimpanzees (Pan troglodytes troglodytes) on gorillas (Gorilla gorilla gorilla) in the wild

Abstract: Intraspecies violence, including lethal interactions, is a relatively common phenomenon in mammals. Contrarily, interspecies violence has mainly been investigated in the context of predation and received most research attention in carnivores. Here, we provide the first information of two lethal coalitionary attacks of chimpanzees (Pan troglodytes troglodytes) on another hominid species, western lowland gorillas (Gorilla gorilla gorilla), that occur sympatrically in the Loango National Park in Gabon. In both ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 87 publications
(142 reference statements)
1
12
1
Order By: Relevance
“…We did not observe gorillas or chimpanzees emitting alarm calls in response to the arrival of the other ape species to a subgroup. No predation attempts between the ape species were observed in this study, but chimpanzees at Loango have been observed killing infant gorillas on two occasions ( Southern et al., 2021 ). However, we did observe bidirectional aggressive threats and contact agonism between apes in the Goualougo Triangle.…”
Section: Resultsmentioning
confidence: 53%
See 3 more Smart Citations
“…We did not observe gorillas or chimpanzees emitting alarm calls in response to the arrival of the other ape species to a subgroup. No predation attempts between the ape species were observed in this study, but chimpanzees at Loango have been observed killing infant gorillas on two occasions ( Southern et al., 2021 ). However, we did observe bidirectional aggressive threats and contact agonism between apes in the Goualougo Triangle.…”
Section: Resultsmentioning
confidence: 53%
“…Increased size of interspecific groups could reduce the risk of predation without the increased feeding and mating competition associated with larger groups of conspecifics. Furthermore, recent reports of chimpanzees killing immature gorillas ( Southern et al., 2021 ) prompted us to predict that vulnerable gorillas would avoid close interaction with adult chimpanzees if they posed a risk.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prey species with similar anatomy such as monkeys are also potentially informative; Boesch & Boesch [ 79 ] report on a juvenile chimpanzee with a colobus monkey skull using a tool to scoop out the brain, and another case involved an adult female using sticks to clean the eye sockets of a colobus skull after she had finished eating the eyes. Moreover, in some parts of Africa, chimpanzees are sympatric with lowland gorillas (for lethal encounters, see [ 80 ]), and gorilla skeletons, exceedingly similar to chimpanzees, are probably encountered. Naturally, being the largest extant land mammal, on dying, elephants leave the largest skulls in their habitats (roughly twice as large as a hippopotamus or a rhinoceros), the only other skulls that bear a superficial resemblance to theirs are those of their closest living relatives, the sirenians (dugongs and manatees) which, being strictly aquatic species, do not share the same habitats.…”
Section: Discussionmentioning
confidence: 99%